Let me put this here, as it's so simple that everyone can take a look at it. I must be blind not to see my misconclusion, but look for yourself(adsbygoogle = window.adsbygoogle || []).push({});

Let [tex]a^TA^\dag b := (a^TAb)^*[/tex] be the definition of the adjoint [tex]A^\dag[/tex].

I thus conclude that

[tex] \underbrace{a^T A^\dag }_{\tilde a^T} \underbrace{B^\dag b}_{\tilde b} = \tilde a^T B^\dag b \stackrel{\text{ex vi termini}}{=}(\tilde a^T B b)^* = (a^T A^\dag B b)^*[/tex]

[tex]\ldots \qquad= a^T A^\dag \tilde b \stackrel{\text{ex vi termini}}{=}(a^T A \tilde b)^* = (a^T A B^\dag b)^*[/tex]

Which is generally true and thus [tex]A^\dag B = A B^\dag[/tex] which is nonsense!?

Edit: Darn, I got the definition of the adjoint wrong, so my conclusion is correct.

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Adjoint magic? Absurdity from nothing?

Can you offer guidance or do you also need help?

Draft saved
Draft deleted

**Physics Forums | Science Articles, Homework Help, Discussion**